Validation of the Readiness for End-of-Life Conversations (REOLC) scale in a German hospital setting - Pia Berlin (PEC Innovation, 2022)
Objective: For every health behavior, readiness to engage is a necessary and crucial foundation for following conversations, interventions or behavior changes. The present study aims to support a one-factor structure for the Readiness for End-of-Life Conversations (REOLC) scale (Berlin et al., 2021) in a population of cancer patients (N = 295). Methods: For validation purposes, data of patients participating in a screening development study at a university clinic was used. Model adequacy was analyzed with structural equation modelling and controlled for with goodness of fit indices: ꭓ2-test, SRMR, rRMSEA. Discriminant and convergent validity were assessed with correlations of REOLC and psychological or health behavior measures. Results: Factor structure was supported with good fit indices, discriminant validity and convergent validity. Readiness correlated significantly with age and reported death anxiety. Conclusion: The REOLC scale is a reliable instrument to assess cancer patients' readiness for end-of-life conversations. Future studies may further address moderating and mediating effects of socio-demographic, medical and psychological factors. Innovation: The assessment of readiness may further indicate anxiety levels of cancer patients and enables practitioners to provide interventions accordingly. However, in a clinical setting and especially for patients with a palliative prognosis, end-of-life care conversations may need to be introduced early.